Pemanfaatan Ekstrak Enzim Kasar Papain dan Bromelin pada Pembuatan Minyak Starter dan Pengaruhnya pada Mutu Virgin Coconut Oil (VCO) Selama Penyimpanan - BARLINA, RINDENGAN; TORAR, DANIEL J. (Pusat Penelitian dan Pengembangan Perkebunan, 2010)
Utilization of Crude Enzyme Extracts, Papain and Bromelain in Starter Oil Making and Its Effects to the Quality of Virgin Coconut Oil (VCO) During StorageResearch was conducted in 2006 at The Indonesian Coconut and Other Palm Research Institute, and at the Institute for Research and Standardization of Trade and Industry, Manado North Sulawesi. Initially starter oil was prepared using two natural enzymes. The research onprocessing VCO using the starter oil with low concentration of crude enzymes was taken place. Research was done in factorial experiment 2 x 4 x 3, using Completely Randomized Design with three replicate. There were 24 units of the experiment. Factor A crude extract of natural enzymes, consists of: A1) crude enzyme extract of papaya fruit peel and, A2) crude enzyme of pineapple fruit extract; Factor B, duration storage, consists of: B1) 0 month, B2) 1 month, B3), 2 months and B4) 3 months. Variables observed consisted of: Rendemen, water content, free fatty acid content, peroxide value and fatty acid profile. The results showed that rendemen of starter oil using crude enzyme papain at concentration of 10-30% ranged 26.10-28.27%. Water content of VCO without storage (0 month) was 0.078% and after one month to three months increased to 0.106% -0.116% (an increase of 35.89% -48.72%). Free fatty acids content of VCO at 0 month 0.073% and after one to three months increased to 0.101% -0.141% (an increase of 35.36% - 93.15%). Highest of peroxide value VCO is using starter oil from the natural enzyme papain, is 1893 meq/kg oil, while the natural enzymes bromelain only 0.704 meq/kg oil. The composition of fatty acids, especially C12 (lauric acid), range 50.35-54.30%. In generally, the results obtained fullfill the APCC standard.